Artemisinin exerts antidepressant-like effects via activation of AKT and ERK signaling pathways - Lin, Ruohong; Zhou, Zhiwei; Jiang, Yizhou; Liu, Song; Xie, Jinfeng; Wang, Haitao; Ulrich, Henning; Zheng, Wenhua (Frontiers in Pharmacology, 2025)
AimsDepression is a leading cause of disability worldwide, with current treatments often limited by efficacy and side effects. Artemisinin (ART), a natural compound with known anti-inflammatory and neuroprotective properties, has not been extensively studied for its potential antidepressant effects. This study aimed to elucidate the neuroprotective mechanisms of artemisinin against corticosterone (CORT)-induced toxicity in PC12 cells model, and to assess its antidepressant-like behavioral effects in a chronic unpredictable mild stress (CUMS) mouse model.MethodsIn vitro, PC12 cells and primary hippocampal neurons were treated with CORT and artemisinin to assess cell viability, oxidative stress, mitochondrial function, and apoptosis. Pharmacological inhibition and CRISPR/Cas9 gene editing were used to explore the roles of AKT and ERK signaling pathways. In vivo, CUMS-induced depression-like behaviors in mice were evaluated using sucrose preference, tail suspension, and forced swim tests. Western blotting and immunohistochemistry studies were performed to analyze molecular mechanisms.ResultsArtemisinin attenuated CORT-induced cytotoxicity, oxidative stress, mitochondrial dysfunction, and apoptosis in PC12 cells and hippocampal neurons. These effects were mediated through the activation of AKT and ERK pathways. In CUMS mice, artemisinin improved depression-like behaviors, upregulated the AKT/GSK/NRF2/HO1 and BDNF/TrkB/ERK/CREB pathways, modulated astrocyte activity, and promoted neurogenesis in the hippocampus.ConclusionArtemisinin exerts significant neuroprotective and antidepressant-like effects through multiple molecular and cellular mechanisms, highlighting its potential as a novel therapeutic agent for depression.